Carboxymethyl chitosan-covalent organic framework-nano-silver composite material as well as preparation method and application thereof
By adding covalent organic skeleton-nano-silver composite materials to the CMCS membrane, the problems of insufficient antibacterial effect and mechanical strength of the CMCS membrane are solved, and the preservation effect of fruits and vegetables is improved, and the aggregation of AgNPs and the constraints of bioreducing agents are avoided.
Patent Information
- Application Number
- CN202411724817.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-03-04
AI Technical Summary
In the prior art, the antibacterial effect and mechanical strength of the carboxymethyl chitosan (CMCS) film are poor, and there are environmental and high energy consumption problems in the synthesis of nano silver particles (AgNPs) by chemical and physical methods, and there are certain limitations in the application of biological reducing agents.
AgNPs were synthesized by biological method using epibiotics as reducing agents, and covalent organic framework-nano-silver composite materials (COFs-AgNPs) were prepared by in-situ growth method. COFs-AgNPs were added to the CMCS matrix to enhance their film-forming ability, antibacterial properties and mechanical properties.
It effectively improves the preservation effect of fruits and vegetables, solves the problems of insufficient antibacterial effect and mechanical strength of CMCS membranes, and avoids the aggregation of AgNPs and the constraints of biological reducing agents, achieving good antibacterial properties of composite membrane materials.
Smart Images

Figure CN119547817A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of biological antibacterial and food packaging materials, and specifically relates to a carboxymethyl chitosan-covalent organic skeleton-nanosilver composite material and a preparation method and application thereof. Background Art
[0002] Fruit and vegetable preservation is a practical technology that provides a suitable storage environment for fruits and vegetables to maintain their life activities, facilitates storage and transportation, and prolongs the shelf life of fruits and vegetables. Fruit and vegetable plastic wrap is a kind of fruit and vegetable preservation technology. It uses natural sugars, proteins and other edible materials as raw materials, and forms a plastic wrap on the surface of fruits and vegetables by wrapping, soaking, coating or spraying, so as to achieve the purpose of fruit and vegetable preservation.
[0003] Carboxymethyl chitosan (CMCS) has the advantages of good film-forming properties, non-toxicity, and biodegradability. It is a food packaging film polymer with good application prospects. However, due to the poor antibacterial effect and mechanical strength of pure CMCS film, its practical application is often subject to certain restrictions. Adding various additives (such as graphene, cellulose, and catechol) to CMCS films can improve their mechanical strength and antibacterial activity. In addition, CMCS has a strong metal binding ability and can bind to a variety of metals (such as TiO 2 , ZnO, MgO, and silver nanoparticles (AgNPs) interact.
[0004] Compared with other metal particles, AgNPs have attracted much attention in food packaging applications due to their high thermal stability, strong antibacterial activity and low volatility. AgNPs can directly interact with sulfur-containing proteins inside and outside the bacterial cell membrane, resulting in changes in the structure or function of the bacterial cell membrane, thereby affecting the viability of bacterial cells. However, the high surface energy of AgNPs makes them easy to agglomerate and deposit, resulting in a decrease in antibacterial effect. In addition, the uncontrolled oxidation behavior of AgNPs may lead to the sudden release of silver ions, which will lead to reduced stability, increased cytotoxicity, environmental hazards, and even exacerbated health and safety issues. Therefore, the incorporation of suitable carriers to immobilize AgNPs can effectively enhance the stability of AgNPs, prevent AgNPs from agglomerating, ensure biosafety, and thus improve the antibacterial effect.
[0005] The superior physical, chemical and biological properties of AgNPs are mainly determined by their structure, crystallinity, shape, composition and size. At present, the strategies for preparing AgNPs mainly include various chemical, physical and biological methods. However, the common disadvantages of chemical and physical synthesis methods are environmental problems and high energy consumption. Bio-based green synthesis technology has gradually become an alternative method for the physical and chemical synthesis of AgNPs due to its advantages such as non-toxicity, environmental protection, economic feasibility and greenness. At present, AgNPs are synthesized by biosynthesis, usually using biological reductants (such as microorganisms, plant extracts, chitosan, starch, algae, etc.) instead of chemical reductants (such as sodium citrate, sodium borohydride, l-tyrosine, gallic acid, triethanolamine, etc.). In addition, some biological reductants (such as fungi, bacteria, algae and plants) have been used to synthesize AgNPs. However, when using bioreductants to synthesize AgNPs, problems such as the transfer of bacterial resistance genes, the emergence of virulence factors, and opportunistic infections are prone to occur. In addition, the effect of bioreductants is easily restricted by the environment's effects on biological activity, thus limiting their further application.
[0006] Therefore, how to develop a new type of composite membrane material that can solve the problems of poor antibacterial effect and mechanical strength of pure CMCS membrane, solve the environmental and high energy consumption problems of chemical and physical synthesis of AgNPs, prevent AgNPs aggregation, and get rid of the existing constraints of bioreductants, so as to achieve effective antibacterial performance of composite membrane materials and effectively improve the preservation effect of fruits and vegetables has become a technical problem to be solved urgently in the present invention. Summary of the invention
[0007] In order to overcome the deficiencies in the prior art, the first purpose of the present invention is to provide a method for preparing a carboxymethyl chitosan-covalent organic framework-nanosilver composite material, which uses postbiotics as a reducing agent to synthesize AgNPs by a biological method; and the COF-AgNPs composite material is prepared by an in-situ growth method, and the ordered porous structure of COF provides specific constraints for AgNPs, thereby effectively avoiding the aggregation of AgNPs; in addition, the present invention adds COF-AgNPs to the CMCS matrix, which not only enhances the film-forming ability of the former, but also gives the latter excellent antibacterial properties and mechanical properties. Therefore, the present invention adopts the above-mentioned preparation ideas to prepare the resulting composite film material, which can effectively improve the preservation effect of fruits and vegetables, thereby comprehensively solving the above-mentioned technical problems.
[0008] The second object of the present invention is to provide a carboxymethyl chitosan-covalent organic skeleton-nanosilver composite material prepared by the above preparation method.
[0009] The third object of the present invention is to provide an application of the above-mentioned carboxymethyl chitosan-covalent organic framework-nanosilver composite material.
[0010] To achieve the above object, in the first aspect of the present invention, the technical solution adopted is:
[0011] A method for preparing a carboxymethyl chitosan-covalent organic framework-nanosilver composite material comprises the following steps:
[0012] (1) stirring and mixing a covalent organic framework material and a silver nitrate solution, then collecting the product, adding a postbiotic solution to the product, adjusting the pH and stirring the product for reaction, and then separating, washing, and drying the product to obtain a covalent organic framework-nanosilver composite material, referred to as COFs-AgNPs;
[0013] The covalent organic framework material is obtained by reacting trialdehyde phloroglucinol and 3,3'-dihydroxybenzidine as organic ligands under acid catalysis; the postbiotic solution is a culture supernatant obtained by ultrasonically crushing a probiotic culture and then centrifuging it; the probiotic is one or more of Lactobacillus rhamnosus LGG, Lactobacillus rhamnosus JL-1, and Lactobacillus plantarum J26;
[0014] (2) uniformly mixing the COFs-AgNPs obtained in step (1) with carboxymethyl chitosan, an additive and water, and then exhausting the air to obtain a composite membrane liquid; drying the composite membrane liquid after forming a film to obtain the carboxymethyl chitosan-covalent organic framework-nanosilver composite material.
[0015] As a preferred embodiment of the present invention, in step (1), the probiotic is Lactobacillus rhamnosus LGG. In the present invention, the postbiotic solution is a fermentation product of treated inactivated probiotics, which retains the substances produced by probiotics, such as polysaccharides, vitamins, amino acids, polypeptides and proteins, as a postbiotic, and also has the possibility of being a reducing agent. The present invention uses a postbiotic preparation as a reducing agent for the first time, and investigates and demonstrates its synthetic effect, which provides a possibility for the biosynthesis of AgNPs.
[0016] As a preferred embodiment of the present invention, in step (1), the concentration of the silver nitrate solution is 0.8 to 1.2 mmol / L; the volume of the silver nitrate solution per mg of the covalent organic framework material is (1.8 to 2.2) mL; the stirring and mixing time is 6 to 10 hours; the pH adjustment is to adjust the system pH to 9.5 to 11.0; the stirring reaction time is 8 to 16 hours; and the drying is vacuum freeze drying.
[0017] Covalent organic frameworks (COF) are a new class of crystalline porous materials formed by covalent bonds of organic precursor molecules. In recent years, COFs have been widely used in catalysis, gas adsorption, biomedicine, environmental analysis, biosensing and other fields due to their adjustable functions, good stability, adjustable pore structure and high specific surface area. In addition, the chemical control and structure of COFs can be achieved by pre-designing organic monomers, making them excellent carriers for loading various active molecules and nanomaterials. However, there are no reports in the prior art of using in situ growth methods to prepare COF-AgNPs composite materials and use them for fruit and vegetable preservation. In the present invention, by preparing special COFs, its porous structure can effectively control the growth of silver nanoparticles and prevent them from aggregating, and experiments have found that the combination of COFs and AgNPs has good antibacterial properties, which reflects great application potential in the design and development of antibacterial packaging. As a preferred solution, in step (1), the molar ratio of trialdehyde phloroglucinol and 3,3'-dihydroxybenzidine during the reaction is (1.8-2.2):(2.8-3.2), more preferably 2:3. As a preferred solution, the temperature of the reaction under acid catalysis is 23-27°C, and the reaction time is 20-30h.
[0018] As a preferred embodiment, in step (1), the preparation method of the probiotic culture is as follows: the probiotics are inoculated in an MRS liquid culture medium at an inoculation rate of 4 v / v% to 6 v / v%, and then activated and cultured at 37±1°C for 20 to 30 hours; the activated and cultured probiotics are inoculated in an MRS liquid culture medium at an inoculation rate of 4 v / v% to 6 v / v%, and subcultured at 37±1°C for 14 to 22 hours to obtain the probiotic culture.
[0019] As a preferred solution, the ultrasonic power of the ultrasonic crushing is 200-500W, and the crushing time is 15-30min; the speed of the centrifugation is 4000-6000rpm, and the centrifugation time is 5-20min.
[0020] As a preferred embodiment, in step (2), the auxiliary agent is propylene glycol.
[0021] As a preferred solution, in step (2), in the composite membrane solution, the ratio of COFs-AgNPs, carboxymethyl chitosan, and additives is (20-100) mg: (1.8-2.2) g: (0.2-0.3) g. As a more preferred solution, in step (2), in the composite membrane solution, the ratio of COFs-AgNPs, carboxymethyl chitosan, and additives is 80 mg: 2 g: 0.25 g.
[0022] The second aspect of the present invention adopts the following technical solution:
[0023] The carboxymethyl chitosan-covalent organic skeleton-nanosilver composite material is prepared by the preparation method.
[0024] The third aspect of the present invention adopts the following technical solution:
[0025] The above-mentioned carboxymethyl chitosan-covalent organic framework-nanosilver composite material is used in the preservation of fruits and vegetables.
[0026] As a preferred solution, when the carboxymethyl chitosan-covalent organic framework-nanosilver composite material is used to preserve fruits and vegetables, the fruits and vegetables to be preserved are immersed in the composite film liquid, and then dried to form a composite preservative film for preserving fruits and vegetables; or, the composite film liquid is coated on the surface of the fruits and vegetables to be preserved, and then dried to form a composite preservative film for preserving fruits and vegetables.
[0027] The present invention does not specifically limit the fruits and vegetables to be preserved, and those skilled in the art can routinely select the types of fruits and vegetables to be preserved. As a preferred solution, the fruits and vegetables are one or more of citrus, grapes, strawberries, tomatoes, and cucumbers, more preferably citrus, and further preferably sugar oranges, which are a type of citrus.
[0028] The above technical solution of the present invention has the following advantages and beneficial effects:
[0029] The preparation method of the carboxymethyl chitosan-covalent organic skeleton-nanosilver composite material provided by the present invention uses the postbiotics of probiotics as a reducing agent to reduce Ag in situ + , silver nanoparticles (AgNPs) are anchored on a covalent organic framework (COF) to prepare a COF-AgNPs composite nanomaterial. Then, CMCS and COF-AgNPs are mixed to prepare a composite film-forming liquid, and finally, after film formation and drying, a carboxymethyl chitosan-covalent organic framework-nanosilver composite material (CMCS@COF-AgNPs) is prepared. The material prepared by the present invention is a new type of composite antibacterial packaging film, which can achieve the preservation of fruits and vegetables by infiltration, coating and the like.
[0030] The present invention uses the postbiotics of probiotics as a reducing agent to synthesize AgNPs through a biosynthetic method. At the same time, trialdehyde phloroglucinol (Tp) and 3,3'-dihydroxybenzidine (DH) are used as organic ligands to synthesize new COFs through Schiff base reaction. The COFs prepared by the present invention have the characteristics of film-like morphology, large pore size, diverse functional sites, good stability, and high specific surface area. Further, the present invention prepares a COF-AgNPs composite material by an in situ growth method. The ordered porous structure of COF provides specific constraints for AgNPs, thereby effectively avoiding the aggregation of AgNPs. Further, the present invention integrates COF-AgNPs as a functional filler into the CMCS matrix, and successfully prepares a new composite material (i.e., CMCS@COF-AgNPs) with excellent antibacterial and mechanical properties. In the above strategy, the present invention adds COF-AgNPs to the CMCS matrix, which not only enhances the film-forming ability of the former, but also gives the latter excellent antibacterial and mechanical properties. Among them, COF plays a key role in preventing AgNPs from aggregating due to its superior specific surface area and adjustable pore size, thereby enhancing the antibacterial properties of CMCS@COF-AgNPs. Therefore, the CMCS@COF-AgNPs prepared by the present invention can exert good fruit and vegetable preservation capabilities after being used for fruit and vegetable preservation.
[0031] The experiment confirmed that the COF-AgNPs composite nanomaterial prepared by the present invention has good antibacterial properties, and exhibits good antibacterial properties against Staphylococcus aureus, Escherichia coli, Bacillus cereus, Cronobacter sakazakii, Listeria monocytogenes and Salmonella. In addition, the CMCS@COF-AgNPs composite film prepared by the present invention has good physical properties, safety and antibacterial activity. The safety test showed that the CMCS@COFs-AgNPs composite film has excellent safety, and the cell survival rate of the composite film with COF-AgNPs added for 24 hours is higher than 85%. Furthermore, taking the preservation of fruits and vegetables of sugar oranges as an example, the experiment of the present invention confirmed that the prepared CMCS@COFs-AgNPs composite film has a good preservation effect on fresh sugar oranges.
[0032] Therefore, the preparation process of the carboxymethyl chitosan-covalent organic skeleton-nanosilver composite material provided by the present invention can not only solve the environmental and high energy consumption problems existing in the chemical and physical synthesis of AgNPs, as well as the problems of poor antibacterial effect and mechanical strength of pure CMCS film, but also prevent AgNPs from aggregating, and get rid of the existing constraints of biological reducing agents, thereby achieving effective antibacterial performance of the composite film material, effectively improving the preservation effect of fruits and vegetables, and having good application prospects in the field of packaging film materials for fruit and vegetable preservation. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1Figures are scanning electron microscope images of AgNPs, COFs and COFs-AgNPs in the present invention; Figure A is a SEM image of AgNPs; Figure B is a SEM image of COFs; Figures C and D are SEM images of COFs-AgNPs at different magnifications;
[0034] Figure 2 The XRD, XPS, high-resolution XPS spectra, FT-IR spectra and N 2 Adsorption isotherm diagram; wherein, Figure a) is the XRD diagram of COF and COF-AgNPs; Figure b) is the XPS diagram of AgNPs, COF and COF-AgNPs; Figure c) is the high-resolution XPS spectrum of C1s in COF-AgNPs; Figure d) is the high-resolution XPS spectrum of N1s in COF-AgNPs; Figure e) is the high-resolution XPS spectrum of O1s in COF-AgNPs; Figure f) is the high-resolution XPS spectrum of Ag3d in COF-AgNPs; Figure g) is the FT-IR spectrum of COF and COF-AgNPs; Figure h) is the N 2 Adsorption isotherms; Figure i) shows the N adsorption of COF-AgNPs. 2 Adsorption isotherms.
[0035] Figure 3 It is a graph showing the inhibitory effect of AgNPs and COF-AgNPs on pathogenic bacteria in the present invention;
[0036] Figure 4 Figure 1 is an antibacterial effect diagram of AgNPs and COF-AgNPs in the present invention; wherein, Figure a) is an SEM image of 6 pathogens treated with COF-AgNPs, Figure b) is a cell membrane potential diagram, Figure c) is a ROS level diagram of 6 pathogens, Figure d) is a cell extracellular protein concentration diagram, and Figure e) is a cell extracellular nucleic acid content diagram (OD 260nm );
[0037] Figure 5It is a synthesis and characterization diagram of the CMCS@COF-AgNPs film of the present invention; wherein, Figure a) is a picture of the CMCS@COF-AgNPs film after CMCS is composited with COF-AgNPs of different contents; Figure b) is a SEM image of the cross section of CMCS and CMCS@COF-AgNPs film; Figure c) is the swelling and solubility of the CMCS@COF-AgNPs composite film; Figure d) is the water vapor permeability (WVP) of the CMCS@COF-AgNPs composite film; Figure e) is the tensile strength of the CMCS@COF-AgNPs composite film; Figure f) is the elongation at break of the CMCS@COF-AgNPs composite film; Figure g) is a cell viability diagram of GES-1 cells cultured on the CMCS@COF-AgNPs composite film;
[0038] Figure 6 It is a diagram of the preservation effect of the CMCS@COF-AgNP composite film of the present invention on sugar oranges; wherein, Figure a) is the appearance of sugar oranges in different treatment groups during storage, Figure b) is the Ag content in the peel and pulp of sugar oranges, Figure c) is the weight result diagram of sugar oranges, Figure d) is the pH result diagram of sugar oranges, and Figure e) is the VC content diagram of sugar oranges. DETAILED DESCRIPTION
[0039] The technical scheme and technical effects of the present invention will be clearly and completely described below in conjunction with specific embodiments and test examples. However, it should be understood by those skilled in the art that the embodiments are only used to illustrate the technical scheme of the present invention and should not be regarded as limiting the scope of protection of the present invention. The test methods used in the following examples are conventional methods unless otherwise specified; the raw materials used are all commonly used in the art, available to the public or commercially available, unless otherwise specified.
[0040] Among them, in the following embodiments, the Lactobacillus rhamnosus LGG involved is a commercial probiotic purchased from Beijing Chr. Hansen. Lactobacillus rhamnosus JL-1 is an existing strain reported in the patent with application number 2023110161441, and the microbial preservation number is GDMCC NO: 62852. Lactobacillus plantarum J26 is an existing strain reported in the patent with application number 2024100401138, and the microbial preservation number is CGMCC NO.5448.
[0041] In the following embodiments, the other strains involved are all comparative strains used in the early strain screening process, which are isolated and identified by the team of the present invention in the early stage. The isolation sources of each comparative strain are shown in Table 1.
[0042] Table 1. Isolation sources of comparative strains
[0043] Species name Separation source / origin Lactobacillus rhamnosus 19-1 Four-month-old baby stool sample Lactobacillus rhamnosus 20-1 Four-month-old healthy baby stool Lactobacillus rhamnosus 20-3 Four-month-old healthy baby stool Lactobacillus rhamnosus 20-37 Four-month-old healthy baby stool Lactobacillus paracasei M-11-6 Traditional dairy products in Tibet Lactobacillus paracasei 100-1 Traditional dairy products in Tibet Lactobacillus paracasei 92-3 Tibetan traditional fermented dairy products Lactobacillus paracasei TD062 Tibetan traditional fermented dairy products Lactobacillus paracasei TD095 Tibetan traditional fermented dairy products Lactobacillus plantarum 43-11 Tibetan traditional fermented dairy products Lactobacillus plantarum 62-15 Tibetan traditional fermented dairy products Lactobacillus plantarum 62-16 Tibetan traditional fermented dairy products Lactobacillus plantarum 100-4 Tibetan traditional fermented dairy products Lactobacillus bulgaricus TD121 Traditional dairy products in Tibet Lactobacillus bulgaricus TD122 Traditional dairy products in Tibet Lactobacillus reuteri J1 Tibetan traditional fermented dairy products Lactobacillus gasseri JM-1 Four-month-old baby stool sample Lactobacillus brevis TD107 Tibetan traditional fermented dairy products Lactobacillus brevis TD108 Tibetan traditional fermented dairy products
[0044] When isolating the control strain, 10 g of the sample was mixed with 90 mL of sterile distilled water, diluted by gradient dilution method, and then spread on a plate containing 0.5% CaCO 3 The strains were incubated on MRS medium at 37°C for 48 hours, and the growth of the strains was observed. The colonies with calcium rings were selected and the total number of colonies was recorded. Different colonies were numbered according to the colony morphology (shape, color, surface, edge, protrusion), and colonies with different morphologies were streaked and cultured three times until they were purified into single colonies. The strain type was then preliminarily determined by morphological observation, Gram staining, and catalase contact test. Finally, the genome was extracted and 16S rDNA sequence analysis was performed to complete the identification of each strain. The 16S rDNA identification results of each strain are shown in Table 2.
[0045] In the following examples, MRS liquid culture medium is from Qingdao Haibo Biotechnology Co., Ltd. and is a conventional commercial product. The chemical formula of carboxymethyl chitosan is C 20 H 37 N 3 O 14 , which is also a conventional commercial product.
[0046] Example 1
[0047] This embodiment provides a carboxymethyl chitosan-covalent organic framework-nanosilver composite material, and the preparation method thereof comprises the following steps:
[0048] (1) Preparation of postbiotic solution: Probiotics (Lactobacillus rhamnosus LGG) were inoculated in MRS liquid culture medium at an inoculum rate of 5 v / v%, and then placed in a 37°C sterile constant temperature incubator for activation culture for 24 hours; the activated probiotics were inoculated in MRS liquid culture medium at an inoculum rate of 5 v / v%, and placed in a 37°C sterile constant temperature incubator for subculture culture for 18 hours; the culture obtained after subculture was ultrasonically disrupted for 20 minutes (ultrasonic power of 400 W), and then the disrupted culture was centrifuged at 5000 rpm for 10 minutes, and the supernatant obtained by centrifugation was taken as the postbiotic solution for later use;
[0049] Preparation of covalent organic framework materials (COFs): 42 mg of trialdehyde pyrogallol, 1.2 mL of aniline, 5 mL of 1,4-dioxane and 1.2 mL of acetic acid aqueous solution (6M) were mixed to obtain an organic ligand solution A; 64.8 mg of 3,3'-dihydroxybenzidine was dissolved in 5 mL of 1,4-dioxane to obtain an organic ligand solution B; the organic ligand solution A and the organic ligand solution B were mixed evenly, and then the obtained mixture was allowed to react at 25±2°C for 24 hours; the crystals obtained after the reaction were first soaked in 1,4-dioxane for 24 hours, then soaked in water for 24 hours, and finally dried to obtain yellow crystals, which are covalent organic framework materials (COFs).
[0050] (2) Preparation of covalent organic framework-silver nanoparticle composites (COFs-AgNPs): 50 mg of COFs obtained in step (1) and 100 mL of AgNO 3 The solution (1 mM) was mixed for 8 hours, and then the solid product was collected and washed with distilled water and ethanol for 3 times respectively; after washing, 10 mL of the postbiotic solution obtained in step (1) was added to the obtained product, the pH was adjusted to 10, and the reaction was stirred overnight (12 hours). When the solution changed from light yellow to golden brown, it indicated that COF-AgNPs were successfully synthesized, and the reaction was stopped; then centrifuged, the obtained golden brown COFs-AgNPs were washed with distilled water and ethanol for 3 times respectively, and finally vacuum freeze-dried to obtain a covalent organic framework-nanosilver composite material (referred to as COFs-AgNPs).
[0051] (3) Preparation of carboxymethyl chitosan-covalent organic framework-silver nanoparticle composite material (CMCS@COF-AgNPs): 80 mg of COFs-AgNPs material (mass concentration 4% (w COF-AgNPs / w CMCS )) and 2g of carboxymethyl chitosan (CMCS) were added into distilled water, and then 0.25g of propylene glycol was added to make the final solution volume 100mL; the obtained solution was mixed evenly by magnetic stirring, and ultrasonic degassing was performed to obtain a composite membrane liquid; the composite membrane liquid was quantitatively spread on a culture dish of standard size and specification to form a film, placed in a constant temperature box at 40°C for drying, and then placed in an ambient humidity of 75% for 24h before the film was peeled off to obtain a composite membrane, which is the carboxymethyl chitosan-covalent organic framework-nanosilver composite material (denoted as CMCS@COF-AgNPs) of Example 1.
[0052] The present invention also provides the application of the carboxymethyl chitosan-covalent organic skeleton-nanosilver composite material in the preservation of fruits and vegetables; the fruits and vegetables are specifically sugar oranges among citrus varieties.
[0053] In other embodiments, the types of fruits and vegetables to be preserved can be other varieties of fruits and vegetables, which are not particularly restricted by the present invention and will not affect the preservation effect of the present invention. For example, in the art, citrus generally includes sugar oranges, mandarin oranges, baba oranges, navel oranges, mandarin oranges, ugly oranges, and other varieties. The composite material of the present invention is applicable to the above varieties. At the same time, the composite material of the present invention is also applicable to the preservation of other types of fruits and vegetables, such as grapes, strawberries, tomatoes, cucumbers, etc.
[0054] Example 2
[0055] This embodiment provides a carboxymethyl chitosan-covalent organic framework-nanosilver composite material, and its preparation method is similar to that of Example 1, except that: in step (1), the probiotics used are replaced by Lactobacillus plantarum J26; in step (2), the amount of COFs-AgNPs material used is 100 mg, and the other process conditions are the same.
[0056] Example 3
[0057] This embodiment provides a carboxymethyl chitosan-covalent organic framework-nanosilver composite material, and its preparation method is similar to that of Example 1, except that in step (1), the probiotics used are replaced by Lactobacillus rhamnosus JL-1, and the other process conditions are the same.
[0058] The application effect of the technical solution of the present invention is described below in conjunction with test examples.
[0059] Experimental Example 1: Identification results of different probiotics and the effects of different postbiotics on the synthesis of AgNPs
[0060] In this experimental example, 22 different probiotics were prepared into postbiotic solutions, which were used as reducing agents to synthesize AgNPs, and the effect of postbiotic types on the synthesis of AgNPs was evaluated by the particle size of AgNPs. The 22 probiotics specifically include: Lactobacillus rhamnosus JL-1, Lactobacillus rhamnosus LGG, Lactobacillus rhamnosus 19-1, Lactobacillus rhamnosus 20-1, Lactobacillus rhamnosus 20-3, Lactobacillus rhamnosus 20-37, Lactobacillus paracasei M-11-6, Lactobacillus paracasei 100-1, Lactobacillus paracasei 92-3, Lactobacillus paracasei TD062, Lactobacillus paracasei TD095, Lactobacillus plantarum J26, Lactobacillus plantarum 43-11, Lactobacillus plantarum 62-15, Lactobacillus plantarum 62-16, Lactobacillus plantarum 100-4, Lactobacillus bulgaricus TD121, Lactobacillus bulgaricus TD122, Lactobacillus reuteri J1, Lactobacillus gasseri JM-1, Lactobacillus brevis TD107, Lactobacillus brevis TD108. The 16S rDNA sequencing results of each strain are shown in Table 2.
[0061] The synthesis steps of AgNPs are as follows: ① Different types of probiotics are inoculated in MRS liquid culture medium at an inoculation rate of 5 v / v%, and then placed in a sterile constant temperature incubator at 37°C for activation culture for 24 hours; the probiotics after activation culture are inoculated in MRS liquid culture medium at an inoculation rate of 5 v / v%, and placed in a sterile constant temperature incubator at 37°C for subculture culture for 18 hours; the culture obtained by subculture is ultrasonically disrupted for 20 minutes, and after disruption, the culture is centrifuged at 5000 rpm for 10 minutes, and then the supernatant obtained by centrifugation is taken to obtain postbiotic solutions of different probiotics.
[0062] ② The postbiotic solutions of different probiotics were mixed with 1mM AgNO 3 The solutions were mixed in a conical flask at a volume ratio of 1:10, and then the pH was adjusted to 10 with 1 mol / L NaOH and stirred overnight (12 h) in a magnetic stirrer; when the solution changed from light yellow to brownish yellow, it indicated that AgNPs were successfully synthesized.
[0063] The synthesized AgNPs solution was centrifuged in a high-speed centrifuge at 12000rpm for 20min, the supernatant was discarded and the precipitate was retained, and then distilled water was added to the precipitate and centrifuged and washed twice to ensure that the AgNPs particles were fully precipitated. The obtained AgNPs product was precooled in a -80℃ refrigerator and then placed in a freeze dryer for full freeze drying for 24h to obtain AgNPs powder. The particle size test of the AgNPs powder prepared from the postbiotic solution of different probiotics was performed, and the particle size test results are shown in Table 2.
[0064] Table 2. Bacterial species identification results and particle size of AgNPs synthesized by different postbiotics
[0065]
[0066]
[0067] As shown in Table 2, the type of postbiotics has a certain effect on the particle size of the synthesized AgNPs. When the postbiotic type is Lactobacillus rhamnosus LGG, the particle size of the synthesized AgNPs is the smallest, which is 46.22nm. Secondly, the particle size of the AgNPs synthesized by Lactobacillus rhamnosus JL-1 and Lactobacillus plantarum J26 is also less than 70nm, which is conducive to exerting a better antibacterial effect. This is because the antibacterial effect of AgNPs is inversely proportional to its particle size. The smaller the particle size, the larger the specific surface area, and the more conducive it is for more AgNPs particles to bind and penetrate the bacterial cell membrane, thereby exerting an antibacterial effect.
[0068] Experimental Example 2: Structural Characterization of AgNPs, COFs, and COFs-AgNPs Materials
[0069] In this test example, the morphology of AgNPs, COFs, and COFs-AgNPs synthesized in Example 1 and the dispersion of AgNPs in COF were characterized by SEM. Figure 1 As shown. Among them, Figure 1 Among them, (A) is AgNPs; (B) is COFs; (C) and (D) are COFs-AgNPs.
[0070] Depend on Figure 1 It can be seen that Figure 1 As shown in A, the AgNPs particles synthesized using the postbiotic Lactobacillus rhamnosus LGG as a reducing agent are spherical with a relatively uniform particle size, but show obvious aggregation. Figure 1 B shows the morphology of COFs. It can be observed that the prepared COF is in the form of flakes with clear boundaries and a smooth surface, indicating that the crystal structure is neat. Figure 1 C is the SEM image of COFs-AgNPs material at a small magnification, such as Figure 1 As shown in Figure C, the loading of AgNPs has little effect on the overall morphology of COF, and it can be observed that spherical AgNPs particles are loaded on the surface of COF. Figure 1 D is the SEM image of the COFs-AgNPs material at a larger magnification. It can be more clearly observed that the AgNPs particles are successfully loaded on the COFs, are evenly dispersed, and there is no obvious aggregation phenomenon.
[0071] Furthermore, this experimental example used XRD analysis to investigate the crystallinity of COFs and COFs-AgNPs. Figure 2 As shown in a), the strongest peak in COFs appears at 2θ=7.1°, which is a small-angle peak. The peaks in COFs are all sharp, indicating that COFs have good crystal form. When COFs are loaded with AgNPs, all peaks decrease, which may be due to the fact that some AgNPs are combined in the skeleton of COFs, affecting the ordered structure of COFs. In addition, Figure 2 In a), four obvious characteristic diffraction peaks of AgNPs can be clearly observed, and their positions are 38.1°, 44.3°, 64.2°, and 77.4°, corresponding to the (111), (200), (220), and (311) crystal planes of silver, respectively. In the XRD pattern of COFs-AgNPs, obvious characteristic peaks of AgNPs also appear at the corresponding positions, indicating that AgNPs have been successfully integrated into the skeleton of COFs without affecting the crystal form of COFs.
[0072] XPS was used to further characterize the elemental composition and chemical state of COFs and COFs-AgNPs. Figure 2b) shows four obvious characteristic peaks of C1s (285.19 eV), N 1s (400.009 eV), O 1s (531.76 eV) and Ag 3d (368.22 eV), thus confirming the presence of C, N, O and Ag elements.
[0073] like Figure 2 As shown in c), in the high-resolution XPS spectrum, the C1s spectrum of COFs-AgNPs exhibits three discrete component peaks with binding energies of 284.8 eV, 286.25 eV, and 288.42 eV, respectively, which are attributed to CC / C=C, CN / CO, and C=N / C=O. Figure 2 As shown in d), in the N1s spectrum, the binding energies of 398.86 eV, 399.92 eV, and 400.74 eV correspond to C=N, CN, and -NH, respectively. Figure 2 As shown in e), in the O1s spectrum, the characteristic peaks at 531.16 eV and 533.36 eV correspond to C=O and CO, respectively. Figure 2 f) shows that the combination of 374.01eV and 368eV is Ag 0 Ag3d 3 / 2 and Ag3d 5 / 2 These results confirm the successful anchoring of AgNPs in COFs.
[0074] FT-IR spectra of COFs and COFs-AgNPs nanomaterials Figure 2 g). For COFs, 1290 cm -1 and 1610cm -1 The peak at 1440cm indicates the simultaneous existence of CN stretching and C=N bond, which confirms that there is a process of conversion of enol structure to keto structure in the reaction of synthesizing COFs. The CC bond and C=N bond on the straight chain of the skeleton are converted to C=C bond and CN bond respectively through tautomerism. -1 The signals at 1610, 1440 and 1290 cm-1 in the FT-IR spectrum of COFs-AgNPs are attributed to the characteristic stretching bands of aromatic C=C. -1 The absorption intensity of the characteristic peaks at 47° decreased significantly, which may be due to the combination of AgNPs and active groups.
[0075] The nitrogen adsorption isotherms of the samples at 77 K were verified, and the nitrogen adsorption-desorption curves of COFs and COFs-AgNPs were obtained as shown in Figure 2 h) and 2i). COFs exhibit a typical IV-type isotherm, indicating that COFs are materials with coexisting micropores and mesopores. The specific surface area of COFs was measured to be 172.8 m 2·g -1 The specific surface area of COFs-AgNPs is 50.39 m 2 ·g -1 , significantly reduced by 122.41m 2 ·g -1 The pore size slightly decreased from 5.23nm to 3.4nm, which indirectly shows that AgNPs are not loaded through the pores of COFs, but are loaded on COFs through coordination, blocking some pores and causing a significant decrease in specific surface area.
[0076] Experimental Example 3: Evaluation of the antibacterial effects of AgNPs and COFs-AgNPs on the tested bacteria
[0077] This test example investigates the inhibition of AgNPs and COFs-AgNPs in Example 1 on six test bacteria, including Staphylococcus aureus, Escherichia coli, Bacillus cereus, Cronobacter sakazakii, Listeria monocytogenes and Salmonella. The inhibition zones of AgNPs and COFs-AgNPs on pathogenic bacteria are shown in Figure 1. Figure 3 shown.
[0078] Depend on Figure 3 It can be seen that Staphylococcus aureus showed high sensitivity to both AgNPs and COFs-AgNPs, with the diameters of their inhibition zones being 15.32 mm and 16.23 mm, respectively. AgNPs and COFs-AgNPs had weaker inhibitory effects on Salmonella, with the inhibition zones being only 8.53 mm and 9.82 mm, respectively. The diameters of the inhibition zones of COFs-AgNPs on Staphylococcus aureus, Escherichia coli, Bacillus cereus, Cronobacter sakazakii, Listeria monocytogenes and Salmonella were 0.91 mm, 1.03 mm, 1.54 mm, 0.67 mm, 0.74 mm and 0.56 mm larger than those of AgNPs, respectively. Compared with AgNPs, COFs-AgNPs showed better inhibition rates against the six tested bacteria, indicating that immobilizing AgNPs on COFs can effectively improve the antibacterial effect against the six pathogenic microorganisms.
[0079] Furthermore, the minimum inhibitory concentration (MIC) results of AgNPs and COF-AgNPs against 6 pathogens are shown in Table 3. Note: In Table 3, “+” represents that the solution in the well plate is turbid and bacteria grow; “-” represents that the solution in the well plate is clear and transparent and there is no bacterial growth.
[0080] Table 3 Minimum inhibitory concentration (MIC) of AgNPs and COF-AgNPs against 6 pathogens
[0081]
[0082] As shown in Table 3, Staphylococcus aureus was most sensitive to AgNPs and COFs-AgNPs, with MICs of 25μg / mL and 12.5μg / mL, respectively; the MICs for Escherichia coli were both 25μg / mL; and the MICs for Bacillus cereus were 50μg / mL and 25μg / mL, respectively. The MICs of AgNPs for Cronobacter sakazakii and Listeriamonocytogenes were both 200μg / mL; while the MICs of COFs-AgNPs for Cronobacter sakazakii and Listeriamonocytogenes were both 100μg / mL. The MICs of AgNPs and COFs-AgNPs for Salmonella were the highest, at 400μg / mL. Bacteria grew at all concentrations in the saline control group. In general, COFs-AgNPs had better inhibitory effects on the six bacterial species than AgNPs, and the results were consistent with the above inhibition zone results.
[0083] Experimental Example 4: Discussion on the Antibacterial Mechanism of COFs-AgNPs
[0084] In order to further explore the antibacterial mechanism of COFs-AgNPs, this experiment used SEM to observe the morphological changes of six bacteria, Staphylococcus aureus, Escherichia coli, Bacillus cereus, Cronobactersakazakii, Listeria monocytogenes and Salmonella, after being treated with COFs-AgNPs. Figure 4 As shown in a), the 6 bacterial cells in the normal group that were not treated with COFs-AgNPs all showed a smooth surface, Staphylococcus aureus was spherical, and the other bacterial cells were rod-shaped. After being treated with 1MIC of COFs-AgNPs, the morphology of the 6 bacterial cells changed significantly, with wrinkles on the surface of the bacterial cells, some cells were damaged, and some of the cell contents flowed out.
[0085] Furthermore, the present invention uses DiBAC4 (3) probe to detect the effects of AgNPs and COFs-AgNPs on the cell membrane potential of six bacterial species, including Staphylococcus aureus, Escherichia coli, Bacillus cereus, Cronobacter sakazakii, Listeria monocytogenes and Salmonella. Figure 4 As shown in b), compared with the fluorescence intensity of the untreated 6 bacteria, the fluorescence intensity of the DiBAC4(3) probe in the cells was significantly increased after treatment with 1 MIC of AgNPs and COFs-AgNPs (P < 0.05). After treatment with COFs-AgNPs, the fluorescence intensity of DiBAC4(3) in Salmonella, Listeria monocytogenes, Bacillus cereus, Cronobacter sakazakii, Escherichia coli and Staphylococcus aureus increased by 3.57, 3.24, 4.08, 5.01, 4.96 and 4.63 times, respectively. The fluorescence intensity of Listeria monocytogenes, Bacillus cereus and Staphylococcus aureus treated with AgNPs was significantly different from that treated with COFs-AgNPs (P < 0.05). The above results show that both AgNPs and COFs-AgNPs lead to increased fluorescence intensity of the six bacteria, depolarization of the cell membrane, and rupture of the lipid bilayer of the cytoplasmic membrane of the six bacteria due to depolarization of the cell membrane, leading to cell death. Among them, the depolarization of the bacteria in the COFs-AgNPs treatment group was stronger, indicating that the cell damage was more obvious.
[0086] Furthermore, the present invention used a blank control group, 1MIC AgNPs added to LB liquid culture, and 1MIC COFs-AgNPs added to LB liquid culture medium and co-cultured with the six test bacteria at 37°C for 8 hours. The ROS kit was used to detect the changes in the intracellular ROS content of Salmonella, Listeria monocytogenes, Bacillus cereus, Cronobacter sakazakii, Escherichia coli, and Staphylococcus aureus. The results are as follows: Figure 4 c). Figure 4c) Compared with the blank control group, the intracellular ROS content of 6 bacteria, including Salmonella, Listeria monocytogenes, Bacillus cereus, Cronobacter sakazakii, Escherichia coli and Staphylococcus aureus, in the 1MIC AgNPs treatment group and the 1MIC COFs-AgNPs treatment group increased significantly (P < 0.05). The relative fluorescence intensity of Bacillus cereus treated with 1MIC AgNPs and 1MIC COFs-AgNPs increased by 39.33% and 62.67% respectively compared with the blank control group (P < 0.05). The relative fluorescence intensity of Listeria monocytogenes treated with 1MIC AgNPs and 1MIC COFs-AgNPs increased by 28.33% and 39.00% respectively (P<0.05) compared with the blank control group, and the relative fluorescence intensity of Salmonella treated with 1MIC AgNPs and 1MIC COFs-AgNPs increased by 31.33% and 35.33% respectively (P<0.05) compared with the blank control group. The relative fluorescence intensity of Cronobacter sakazakii treated with 1MIC AgNPs and 1MIC COFs-AgNPs increased by 25.00% and 25.33% respectively (P<0.05) compared with the blank control group. The relative fluorescence intensity of Escherichia coli and Staphylococcus aureus treated with 1MIC AgNPs and 1MIC COFs-AgNPs increased significantly compared with the blank control group, both exceeding 60.00%. Compared with the 1MICAgNPs-treated group, the intracellular ROS content in the 1MIC COFs-AgNPs-treated group increased more, indicating that 1MIC COFs-AgNPs treatment caused more severe oxidative stress in the cells, affecting the normal physiological metabolic activities of the bacteria and ultimately leading to cell death.
[0087] Furthermore, the present invention tests the extracellular protein concentration of cells in each group of experiments, and the results are as follows: Figure 4 d). Figure 4d) Compared with the blank control group, the extracellular protein leakage of the six tested strains Bacillus cereus, Listeria monocytogenes, Salmonella, Cronobacter sakazakii, Escherichia coli and Staphylococcus aureus increased to varying degrees after being treated with AgNPs and COFs-AgNPs at a concentration of 1 MIC, respectively (P < 0.05). After being treated with 1 MIC of AgNPs, the protein content in the six bacterial cell solutions increased from 0.80, 0.72, 0.71, 0.78, 0.88 and 0.91 μg / mL to 1.29, 1.21, 1.24, 1.26, 1.42 and 1.46 μg / mL, respectively. After COFs-AgNPs treatment, the protein content in the six bacterial solutions increased to 1.40, 1.37, 1.26, 1.30, 1.48 and 1.52 μg / mL, respectively. The protein content in the COFs-AgNPs treatment group did not change significantly compared with the AgNPs treatment group, which may be due to the limited protein content in the bacteria.
[0088] Furthermore, the present invention is to test the extracellular nucleic acid content (OD 260nm ) to test, the results are as follows Figure 4 e). Figure 4 As shown in Figure e), under the action of AgNPs and COFs-AgNPs, the absorbance values of the six test strains at 260nm showed an increasing trend with the increase of time. At 12h, the absorbance values of the bacterial solutions after treatment with AgNPs and COFs-AgNPs at 260nm were much higher than the absorbance values at 0h, indicating that macromolecular substances continued to seep out during this period, which also proved the inhibitory effect of AgNPs and COFs-AgNPs on these six strains.
[0089] Experimental Example 5: Synthesis and Characterization of CMCS@COF-AgNPs Composite Film
[0090] This test example mainly characterizes the synthesis results and structure of the CMCS@COF-AgNPs composite membrane. When preparing CMCS@COFs-AgNPs, weigh 20mg, 40mg, 60mg, 80mg and 100mg of COFs-AgNPs material and 2g of CMCS respectively, add them to distilled water, and then add 0.25g of propylene glycol to make the final solution volume 100mL. Mix evenly by magnetic stirring and perform ultrasonic degassing. The composite membrane liquid is quantitatively spread on a culture dish of standard size and specifications to form a cast film, placed in a constant temperature box at 40°C for drying, and then placed in an ambient humidity of 75% for 24 hours before the film is removed to obtain CMCS@COFs-AgNPs composite membranes with different proportions. The test results are as follows Figure 5 As shown in the figure, “CMCS” is pure CMCS film, “CMCS@COFs-AgNP 1 , CMCS@COFs-AgNP 2 , CMCS@COFs-AgNP 3 , CMCS@COFs-AgNP 4 , CMCS@COFs-AgNP 5 ” represent the composite films prepared by adding 20 mg, 40 mg, 60 mg, 80 mg and 100 mg of COFs-AgNPs, respectively.
[0091] Figure 5 a) Color comparison of pure CMCS film and CMCS@COFs-AgNPs composite film with different amounts of COFs-AgNPs added. The results show that the color of the CMCS film comes from COFs-AgNPs and is closely related to the amount of COFs-AgNPs added. The more COFs-AgNPs added, the darker the color.
[0092] Figure 5 b) CMCS membrane and CMCS@COFs-AgNPs composite membrane (specifically CMCS@COFs-AgNPs 4 ) cross-section scanning electron microscope image. The cross-section of the CMCS membrane is relatively smooth and flat, with a dense structure and uniform distribution. The surface morphology of the CMCS / COFs-AgNPs composite membrane is similar to that of the CMCS membrane, but the cross-section is relatively rough, with a clear layered stacking structure and obvious cracks. This may be because the sheet-like composite nanomaterial COFs-AgNPs agglomerates and stacks in the CMCS matrix.
[0093] Figure 5c) Swelling and solubility results of CMCS@COF-AgNPs composite membrane. The dissolution rate and swelling rate of CMCS@COFs-AgNPs composite membrane decreased significantly with the increase of COFs-AgNPs content (P<0.05). When the content of COFs-AgNPs increased from 0 to 3% (w COF-AgNPs / w CMCS ), the swelling ratio of the film slowly decreased from 74% to 59%. When the content of COFs-AgNPs continued to increase to 5% (w COF-AgNPs / w CMCS ), the swelling rate dropped rapidly to 24%. Similarly, the dissolution of pure CMCS film was as high as 46%. When the addition amount of COFs-AgNPs increased to 3%, the swelling of the film first slowly dropped to 36%, and when the addition amount of COFs-AgNPs increased to 5% (w COF-AgNPs / w CMCS ), the swelling ratio of the film dropped sharply to 27% and finally to 15%.
[0094] Figure 5 d) is the water vapor permeability (WVP) of CMCS@COF-AgNPs. The water vapor permeability of pure CMCS film is 10.1 mg·cm -2 ·d -1 , added with 1% to 5% (w COF-AgNPs / w CMCS The water vapor permeability of CMCS@COFs-AgNPs composite films was 9.7, 9.2, 8.9, 8.1 and 7.3 mg·cm -2 ·d -1 With the increase of COFs-AgNPs, it showed a significant decrease (P<0.05), indicating that the addition of COFs-AgNPs inhibited the permeation of water vapor.
[0095] Figure 5 e) is the tensile strength of the CMCS@COF-AgNPs composite film. The tensile strength of the CMCS film without COFs-AgNPs is low, and as the content of COFs-AgNPs increases from 0 to 5% (w COF-AgNPs / w CMCS ), the tensile strength of the CMCS@COFs-AgNPs composite film also increased significantly (P<0.05), and the value gradually increased from 7MPa to 25MPa.
[0096] Figure 5 f) is the elongation at break of the CMCS@COF-AgNPs composite film. The elongation at break of the CMCS film without COFs-AgNPs is as high as 41%. As the content of COFs-AgNPs increases from 0 to 5% (wCOF-AgNPs / w CMCS ), the elongation at break of the CMCS@COFs-AgNPs composite film was significantly reduced (P<0.05), from 41% to 19%.
[0097] Figure 5 g) shows the cell viability of GES-1 cells cultured on CMCS@COF-AgNPs composite membrane. As can be seen from the figure, as the content of COFs-AgNPs increases from 0 to 5% (w COF-AgNPs / w CMCS ), the cytotoxicity also increased, and the cell survival rate decreased accordingly. COF-AgNPs / w CMCS ), the cell survival rate is still above 85%. The concentration of AgNPs has little effect on the cell survival rate, which is basically above 90%. The results show that although the concentration of AgNPs is the main factor affecting cell survival, a high cell survival rate can be guaranteed within a certain concentration range. Therefore, the prepared CMCS@COFs-AgNPs composite membrane has good biocompatibility and can be used in biomedicine.
[0098] Test Example 6: Evaluation of Fruit and Vegetable Preservation Effect
[0099] This test example evaluates the preservation effect of the CMCS@COF-AgNP composite film prepared by the present invention on sugar oranges. In the evaluation, considering the safety and antibacterial properties, 80 mg of COF-AgNPs was added when preparing the CMCS@COF-AgNP film. Referring to the preparation method of Example 1, the prepared composite film was recorded as CMCS@COFs-AgNP. 4 , to study its preservation effect on sugar oranges.
[0100] During the specific test, select a number of sugar oranges of the same size, maturity, and without disease spots and scars on the surface. After cleaning the surface of the sugar oranges, place them on a gauze rack to air dry naturally. Randomly divide them into a blank control group (uncoated group), a CMCS coating group, and a CMCS@COFs-AgNPs composite coating group. The CMCS coating group is to soak the sugar oranges in CMCS (2g / 100mL) for 1 min; the CMCS@COFs-AgNPs composite coating group is to soak the sugar oranges in the composite film liquid prepared by adding 80mg of COF-AgNPs in Example 1 for 1 min; the blank control group is soaked in ultrapure water for 1 min; each group is taken out after soaking, and placed on a gauze rack at room temperature (25±2°C) to dry. The sugar oranges are then placed at room temperature for storage. Figure 6 Evaluation results of the preservation effect of CMCS@COF-AgNP composite film on citrus.
[0101] Figure 6 a) The blank control group, CMCS coating group, CMCS@COFs-AgNP group at different time (0, 3, 6, 9, 12, 15 days) 4 Storage results of sugar oranges treated with composite coating groups. On the third day, the sugar oranges in the blank control group showed obvious shrinkage, while the CMCS coating group and CMCS@COFs-AgNP 4 There was no significant change in the sugar oranges in the composite coating group. On the 9th day of treatment, the CMCS coating group and CMCS@COFs-AgNP 4 The sugar oranges in the composite coating group were wrinkled and had slight black spots. The sugar oranges in the CMCS coating group had large black spots on the 12th day of treatment, while the CMCS@COFs-AgNP 4 Some black spots also appeared in the composite coating group, while the entire peel of the blank control group shrunk and turned black. On the 15th day, the sugar oranges in the composite coating group showed slight rot, while those in the blank control group and the CMCS coating group showed severe rot.
[0102] The migration amount of silver element determines the CMCS@COFs-AgNP 4 The safety of composite coating for preservation of sugar oranges. 4 The silver content in the peel and pulp of the sugar oranges was tested on days 0, 3, 6, 9, 12 and 15 after the composite coating treatment. Figure 6 b) It can be seen that the amount of silver element migration into the sugar orange peel increases with the extension of storage time. On the third day of the experiment, the amount of silver element migration was 0.00364 mg / kg; on the 15th day of the experiment, the amount of silver element migration increased to 0.00798 mg / kg. The amount of silver element migration into the sugar orange pulp also slowly increased with the storage time. On the third day of the experiment, the amount of silver element migration was 0.0006 mg / kg; on the 15th day of the experiment, the amount of silver element migration increased to 0.001 mg / kg, that is, during the experimental period, the CMCS@COFs-AgNP 4 The sugar oranges treated with composite coating are safe and edible.
[0103] Figure 6 c) shows the blank control group, CMCS coating group, CMCS@COFs-AgNP 4Effect of composite coating group treatment on the weight loss rate of sugar oranges. With the extension of storage time, the weight loss rate of each group increased. During the entire storage process, the weight loss rate of the blank control group was always higher than that of the coating group. In the first 9 days of storage, the weight loss of each coating group was faster. From 9 to 15 days, the weight loss rate of the blank control group increased and the weight loss was more obvious, while the weight loss rate of the two coating groups increased slowly and maintained a low weight loss rate. At 15 days of storage, the weight loss rate of the blank control group was significantly higher than that of the coating group, and the weight loss rate was 1.18 times that of the CMCS coating group, which is CMCS@COFs-AgNP 4 1.44 times of the composite coating group. CMCS@COFs-AgNP 4 The weight loss rate of the tangerines in the composite coating group after 15 days of storage was comparable to that of the blank control group after 7.5 days. From the perspective of weight loss rate, CMCS@COFs-AgNP 4 The shelf life of the composite coating group was extended. This shows that the reasonable addition of COFs-AgNPs can reduce the loss of water, reduce the loss of dry matter, and maintain a low weight loss rate.
[0104] Figure 6 d) Demonstration and exploration of CMCS and CMCS@COFs-AgNP 4 Effect of composite coating treatment on pH value of sugar orange. Figure 6 d) As shown in the blank control group, CMCS coating group and CMCS@COFs-AgNP 4 In the composite coating group, the pH value increased rapidly from 0 to 12 days. During the entire storage period, the pH values of the blank group and the coating group were between 3.8 and 5.1, and the pH value of the blank control group was always higher than that of the CMCS coating group and CMCS@COFs-AgNP 4 Composite coating group, CMCS@COFs-AgNP 4 The final pH value of the composite coating group changed the least, increasing by only 1.3. 4 The composite coating can, to a certain extent, maintain the fruit in a better pH range and better preserve the original taste of the fruit.
[0105] CMCS, CMCS@COFs-AgNP 4 Effect of composite coating on vitamin C content in sugar orange Figure 6 e). During storage, the vitamin C content of the three groups of sugar oranges showed a trend of first increasing and then decreasing, and the vitamin C content of all sugar oranges was less than 0 days when the storage time was 15 days. This phenomenon is related to the fact that vitamin C will be continuously consumed during the post-ripening process of sugar oranges. 4The vitamin C content of the composite coating group was in an increasing state from the 0th to the 3rd day of the experiment. From the 3rd to the 6th day, the vitamin C content of the blank control group began to decrease, while the vitamin C content of the CMCS coating group and the CMCS@COFs-AgNP 4 The vitamin C content in the composite coating group is still rising, and the CMCS coating group and CMCS@COFs-AgNP 4 The vitamin C content of the composite coating group began to decrease after the 6th day. In particular, the vitamin C content of the blank control group and the other two coating treatment groups showed a significant decrease. 4 The vitamin C content of the composite coating group of sugar oranges increased first and then decreased during storage, but was eventually consumed at a lower rate. 4 The loss of vitamin C in the sugar oranges in the composite coating group was the least.
[0106] In summary, the preparation method of the carboxymethyl chitosan-covalent organic framework-nanosilver composite material provided by the present invention can not only solve the environmental and high energy consumption problems existing in the chemical and physical synthesis of AgNPs, as well as the problems of poor antibacterial effect and mechanical strength of pure CMCS film, but also prevent AgNPs from aggregating, and get rid of the existing constraints of biological reducing agents, thereby achieving effective antibacterial performance of the composite film material, effectively improving the preservation effect of fruits and vegetables, and having good application prospects in the field of packaging film materials for fruit and vegetable preservation.
[0107] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a carboxymethyl chitosan-covalent organic framework-nanosilver composite material, characterized in that: The following steps are involved: (1) stirring and mixing the covalent organic framework material and the silver nitrate solution, then collecting the product, adding the postbiotic solution to the product, adjusting the pH and stirring the reaction, and then separating, washing, and drying to obtain a covalent organic framework-nanosilver composite material, recorded as COFs-AgNPs; The covalent organic framework material is obtained by reacting trialdehyde phloroglucinol and 3,3'-dihydroxybenzidine as organic ligands under acid catalysis; the postbiotic solution is a culture supernatant obtained by ultrasonically crushing a probiotic culture and then centrifuging it; the probiotic is one or more of Lactobacillus rhamnosus LGG, Lactobacillus rhamnosus JL-1, and Lactobacillus plantarum J26; (2) uniformly mixing the COFs-AgNPs obtained in step (1) with carboxymethyl chitosan, an additive and water, and then exhausting the mixture to obtain a composite membrane liquid; and drying the composite membrane liquid after forming a membrane to obtain the carboxymethyl chitosan-covalent organic framework-nanosilver composite material.
2. The method for preparing the carboxymethyl chitosan-covalent organic framework-nanosilver composite material according to claim 1, characterized in that: In step (1), the concentration of the silver nitrate solution is 0.8-1.2 mmol / L; the volume of the silver nitrate solution for each mg of the covalent organic framework material is (1.8-2.2) mL; the stirring and mixing time is 6-10 h; the pH adjustment is to adjust the system pH to 9.5-11.0; the stirring reaction time is 8-16 h; and the drying is vacuum freeze drying.
3. The method for preparing the carboxymethyl chitosan-covalent organic framework-nanosilver composite material according to claim 1, characterized in that: In step (1), the molar ratio of trialdehyde phloroglucinol and 3,3'-dihydroxybenzidine during the reaction is (1.8-2.2): (2.8-3.2); the reaction temperature under acid catalysis is 23-27°C and the reaction time is 20-30h.
4. The method for preparing the carboxymethyl chitosan-covalent organic framework-nanosilver composite material according to claim 1, characterized in that: In step (1), the preparation method of the probiotic culture is as follows: the probiotics are inoculated in an MRS liquid culture medium at an inoculation rate of 4 v / v% to 6 v / v%, and then activated and cultured at 37±1°C for 20 to 30 hours; the probiotics after activation and culture are inoculated in an MRS liquid culture medium at an inoculation rate of 4 v / v% to 6 v / v%, and subcultured at 37±1°C for 14 to 22 hours to obtain the probiotic culture; the ultrasonic power of the ultrasonic crushing is 200 to 500 W, and the crushing time is 15 to 30 minutes; the centrifugal speed is 4000 to 6000 rpm, and the centrifugal time is 5 to 20 minutes.
5. The method for preparing the carboxymethyl chitosan-covalent organic framework-nanosilver composite material according to any one of claims 1 to 4, characterized in that: In step (2), the auxiliary agent is propylene glycol.
6. The method for preparing the carboxymethyl chitosan-covalent organic framework-nanosilver composite material according to any one of claims 1 to 4, characterized in that: In step (2), in the composite membrane solution, the dosage ratio of COFs-AgNPs, carboxymethyl chitosan and auxiliary agent is (20-100) mg: (1.8-2.2) g: (0.2-0.3) g.
7. A carboxymethyl chitosan-covalent organic framework-nanosilver composite material prepared by the preparation method according to any one of claims 1 to 6.
8. An application of the carboxymethyl chitosan-covalent organic framework-nanosilver composite material as claimed in claim 7, characterized in that: Application in fruit and vegetable preservation.
9. The use of the carboxymethyl chitosan-covalent organic framework-nanosilver composite material according to claim 8, characterized in that: When the carboxymethyl chitosan-covalent organic framework-nanosilver composite material is used to preserve fruits and vegetables, the fruits and vegetables to be preserved are immersed in the composite film liquid, and then dried to form a composite preservative film for preserving the fruits and vegetables; or the composite film liquid is coated on the surface of the fruits and vegetables to be preserved, and then dried to form a composite preservative film for preserving the fruits and vegetables.
10. Use of the carboxymethyl chitosan-covalent organic framework-nanosilver composite material according to claim 8 or 9, characterized in that: The fruits and vegetables are one or more of citrus, grapes, strawberries, tomatoes and cucumbers.
Citation Information
Cited By
Probiotic-bioactive component composite membrane as well as preparation method and application thereof
CN121495366A